Service required for elderly receiving home care: a situational analysis - Faroogh Na'emani; Ahmad Fayaz-Bakhsh; Zahra Sohrabi; Morad Esmaiil Zali (Payesh, 2019)
Objective (s): The elderly people consume much of the home health care. Therefore how to organize home care services and identify the services needed is important in order to manage and control resources. The purpose of this study was to describe home health services status in Tehran, Iran. Methods: A sample of elderly people receiving home health care during April 2017 to September 2017 was studied. The data was collected using a checklist. Data was entered into SPSS V.19 and analyzed by descriptive statistics. Results: In all 278 elderly people were studied. Of these 59.4% were female and 65.2% were married and their mean age was 81 ± 2.5 years. The results showed that the most frequent services that needed were nursing service (55.4%), physician visit (17.0%) physiotherapy (15.0%). Medical services had a significant statistical relationship with the age and marital status of the elderly but non-medical services (physiotherapy, nursing and laboratory) had a significant relationship with gender, age, marital status and education (p≤0.05). Conclusion: The findings showed that elderly people needed a variety of services. Also there were differences in the use of home health care among the elderly by age, gender, and other demographic factors. Overall, it is necessary for health care providers to understand the growth of the elderly population in the country and their needs in the coming years in order to plan appropriate programs and actions.